Evolução da atividade cromosférica, abundância de lítio e rotação das estrelas análogas e gêmeas solares - Silva, Francys Anthony da (2013)
The study of solar-type stars also includes the familiar solar analogs and twins. These objects have been one of the major research subjects in astrophysics nowadays. A direct comparison of solar activity with chromospheric activity indices for a set of stars very similar to the Sun (twins and analogs) provides an excellent opportunity to study the evolution of stellar activity on timescales of the order of the lifetime on the main sequence. This work deals with the relationship between the abundance of lithium, chromospheric activity, X-ray emission and rotation period in terms of stellar ages. We explore the influence of stellar evolution in the global properties of the stars and the aspects linked to its coronal, chromospheric and magnetic activity. Our main objective is to probe the law of decay of each of these parameters based on a sample of stars classified as well-connected as analogs stars and solar twins.